[PS 01-28] AT2-RECEPTOR STIMULATION PROMOTES NO RELEASE THROUGH eNOS SERINE1177 PHOSPHORYLATION AND eNOS TYROSINE657 DEPHOSPHORYLATION. (September 2016) - Peluso, Antonio; Bertelsen, Jesper; Andersen, Kenneth; Mortensen, Tenna; Hansen, Pernille; Santos, Robson; Steckelings, Ulrike
Abstract : Objective: Angiotensin AT2 receptor (AT2R) stimulation promotes vasodilation by increased nitric oxide (NO) release from endothelial cells. However, the mechanisms underlying AT2R-induced NO synthesis are still not completely characterized. We investigated whether AT2R-stimulation activates endothelial NO synthase (eNOS) by phosphorylation at Ser1177 or dephosphorylation at Tyr657 thus increasing the production of NO, and the participation of phosphatases in mediate these effects. Design and Method: Human Aortic Endothelial Cells (HAEC) were stimulated with the AT2R-agonist C21 (1 μM) in the presence or absence of PD123319 (10 μM) (an AT2R antagonist), L-NAME (10 μM) (an eNOS inhibitor), okadaic acid (10 nM; serine/threonine phosphatase inhibitor) or sodium orthovanadate (10 nM; tyrosine phosphatase inhibitor). NO release was estimated by quantifying DAF-FM fluorescence over a period of 10 minutes. HAEC cells were also stimulated with C21 and intracellular calcium transient analysis was performed using FURA-2 probe. Furthermore, HAEC cells were stimulated with C21 1 μM for 5, 10, 15 minutes, 24 and 48 hours, and expression of phospho-Ser1177-eNOS (activation site), phospho-Tyr657-eNOS (inhibition site) and total eNOS determined by Western blotting. Best time response of eNOS activation using C21 was performed again in presence of PD123319. Results: Stimulation of HAEC by C21 resulted in a significant increase in NO release, which was blocked by PD123319 or L-NAME preincubation. Both phosphatase inhibitors were also able to block the increase in NO release promoted by AT2R stimulation. No intracellular calcium transient was observed after C21 stimulation. Moreover, a significant increase in Ser1177-eNOS phosphorylation which was blocked by PD123319, as well as a significant decrease in Tyr657-eNOS dephosphorylation was observed. AT2R stimulation did not alter expression of total eNOS. Conclusions: From these data, it was concluded that AT2R-stimulation increases NO synthesis by endothelial cells through modulation of eNOS phosphorylation resulting in increased eNOS activity, but not by modulation of total eNOS expression. This pathway is not mediated via intracellular calcium transient.